Analysis of the impact of drilling geothermal wells on groundwater on the example of the Łodz region - Noga, Bogdan (Instal, 2023)
The article presents an analysis of the possibility of groundwater (mainly thermal water) up to a depth of 2,800 meters located in the Lodz area. During the drilling of a geothermal well, several aquifers are drilled and in the Lodz region, the highest aquifers contain water for drinking purposes for the city of Lodz. The work was created as a result of emerging theories that the exploitation of thermal waters located at a depth of about 2,800 meters could affect the contamination of drinking water located at a depth of about 800. To dispel any doubts in this regard, the process of drilling a geothermal well was analyzed. The absence of the possibility of mixing of water from the various aquifers, both at the stage of drilling the well and during its subsequent operation, is ensured by a properly designed and constructed geothermal well.
Keywords: geothermal; geothermal borehole; geothermal heat; geothermal installation